The Effect of Online Guest Review, Hotel Facilities and Online Travel Agent Price On Decision To Stay At Grand Rocky Hotel Bukittinggi : The Case Of Traveloka - Azulmi, Desy; Nursiana, Adinoto; Ingkadijaya, Rahmat (Institut Pariwisata Trisakti, 2018)
Technological developments have shifted the behavior of offline bookings to worldwide online booking, including in Indonesia. This country is currently experiencing a significant increase in the number of Online Travel Agents such as Traveloka. In this website, people can see reviews from previous guests on the strengths and weaknesses of the hotel, and it facilitates people to select a hotel matching to their needs and preferences. Previous research proves that online reviews and facilities affect the guest’s stay decisions. This research aims to determine the effect of online reviews, hotel facilities and prices on the decision to stay at the Grand Rocky Hotel Bukittinggi. The method used in this research is a qualitative method to obtain comprehensive, valid, reliable and objective data. The sample used in this research were 100 guests who stayed at the Grand Rocky Hotel with the reservation through Traveloka. Sample selection was based on purposive sampling technique, and data collection was conducted by Likert questionnaires to investigate the effect of online reviews, facilities and prices on the decision to stay. The results reveals online reviews, hotel facilities and prices have a strong influence on the decision to stay. Therefore, online reviews, facilities, and competitive prices serve as marketing tools to increase hotel revenues from the Online Travel Agent.